2021
DOI: 10.1111/ajag.13028
|View full text |Cite
|
Sign up to set email alerts
|

Situating Eden—Culture change in residential aged care: A scoping review

Abstract: Objective This review explored the knowledge of the Eden Alternative [Eden] as a well‐being model for aged care and the current research of relationship‐centred care in a residential setting to identify gaps in the literature. Methods The search commenced in July 2017 and was updated in January 2020. Eight electronic databases were systematically searched for peer‐reviewed studies published in English between 2000 and 2020. The search revealed 13 papers for final inclusion. Results The Eden model has the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…21 A literature review of culture change models in the United States, the UK, Canada and Australia demonstrated that collaborative relationships between residents, staff and family members are indicators of a successful aged care culture. 22 Involvement of family in the coordination of resident care was found to have positive benefits for both the resident and family dynamics and the relationship with staff and the service. 16,23 Overall, prioritising staff-family relationships has been found to reduce negative outcomes and to have a beneficial effect on not only the care environment, but also the workforce's perceptions of family caregivers, resulting in improved relationships and reduced complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in North America have shown that when communication between staff and carers is prioritised, there are improved quality of life outcomes for residents 21 . A literature review of culture change models in the United States, the UK, Canada and Australia demonstrated that collaborative relationships between residents, staff and family members are indicators of a successful aged care culture 22 . Involvement of family in the coordination of resident care was found to have positive benefits for both the resident and family dynamics and the relationship with staff and the service 16,23 .…”
Section: Introductionmentioning
confidence: 99%